La crisis de la economía, el trabajo y la empresa, una aproximación desde la antropología donal en Leonardo Polo - Guerra Lamadrid, Priscila Sulkerine (Mercurio Peruano, 2020)
This research explains the personal donal structure according to Leonardo Polo’s Transcendental Anthropologhy and gives details on how you can see the dynamics of donation in economy, work and business. Thus, it is proposed a different way to understand this three areas from recognizing of personal ability to give oneself to others, within society.